Algebraic entropy, symmetries and linearization of quad equations consistent on the cube. Issue 4 (1st October 2016) - Gubbiotti, G.; Scimiterna, C.; Levi, D.
Abstract : We discuss the non–autonomous nonlinear partial difference equations belonging to Boll classiﬁcation of quad graph equations consistent around the cube. We show how starting from the compatible equations on a cell we can construct the lattice equations, its Bäcklund transformations and Lax pairs. By carrying out the algebraic entropy calculations we show that the H 4 trapezoidal and the H 6 families are linearizable and in a few examples we show how we can effectively linearize them.